2008
DOI: 10.1111/j.1469-0691.2008.02032.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of emm types 1 and 12 from invasive Streptococcus pyogenes disease in Greece—results of enhanced surveillance

Abstract: Among a total of 101 isolates from the first systematic multicentre surveillance effort concerning invasive Streptococcus pyogenes disease in Greece, conducted between 2003 and 2005 and covering 38% of the population, emm types 1 and 12 were prevalent, being responsible for 27 and nine cases, respectively. The isolates from the remaining 65 cases were assigned to 26 other emm types. Erythromycin resistance (12 isolates) was primarily mef(A)-mediated, although all emm type 1 strains were susceptible. Tetracycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…The majority (65%) of erythromycin-resistant isolates belonged to emm types 58 and 92. Other studies have found erythromycin resistance associated with emm types 4, 11, and 28 (15,16,18,21,42). Resistance to both tetracycline and erythromycin was associated with emm types 58 and 94, of which emm58 was more common (78%).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The majority (65%) of erythromycin-resistant isolates belonged to emm types 58 and 92. Other studies have found erythromycin resistance associated with emm types 4, 11, and 28 (15,16,18,21,42). Resistance to both tetracycline and erythromycin was associated with emm types 58 and 94, of which emm58 was more common (78%).…”
Section: Discussionmentioning
confidence: 92%
“…To date, Ͼ200 different emm types have been reported. In most countries, emm types 1, 3, 12, and 28 have traditionally been associated with invasive GAS disease (9,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%
“…1,2 The M phenotype is the predominant phenotype in many countries, 7,15,19,34,37 whereas iMLS is the most common phenotype in some countries 4,14,25,30 . Differences among the countries could be due to different antibiotic using patterns.…”
Section: Discussionmentioning
confidence: 99%
“…3,10 In some studies, tetracycline resistance in S. pyogenes was found to be associated with the tetM gene and, less frequently, with the tetO gene. 16,29,34 Since tetracycline resistance genes can reside in mobile genetic elements that carry macrolide resistance genes, the cooccurrence of resistance to both classes of drugs is possible. 5 Particularly, a linkage between erm(B) and tet(M) is well known.…”
Section: Discussionmentioning
confidence: 99%
“…This surveillance covered both adult and paediatric cases and presented for the first time data from Greece, as part of the Strep-EURO initiative [1]. Preliminary observations regarding the epidemiology within each age group led us to further investigate possible epidemiological and clinical differences of iGAS infections between the two groups, during the extended period of 2003-2007, as similar comparable data are scarce in the literature and the majority of previous studies simply presented results on overall iGAS infections, or compared invasive and superficial infections [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%